Prominent nephrocalcinosis leading to end-stage kidney disease in a young female with eating disorder: A case report - Takahiko Hoshino; Takahiro Uchida; Takashi Sakai; Minami Koizumi; Mitsuya Mukae; Tadasu Kojima; Muneharu Yamada; Takaya Matsushita; Takashi Oda (Elsevier, 2024)
A Japanese female in her 20 s with a history of self-induced vomiting was diagnosed with severe renal failure and referred to our department. She was extremely lean, with a body mass index of 9.6 kg/m2. Computed tomography showed increased brightness of the entire renal parenchyma; renal biopsy demonstrated prominent calcium deposition in the Bowman's capsule and tubulointerstitial areas accompanied by collapsed glomeruli, severe interstitial fibrosis and tubular atrophy. Although the diagnosis was nephrocalcinosis, no underlying conditions were found. Despite the management of chronic kidney disease-mineral bone disorder and nutritional therapy, the patient developed uremia and initiated maintenance hemodialysis approximately two years after the first visit. Kidney disorders are commonly observed in patients with eating disorders and may occasionally lead to end-stage kidney disease. However, detailed investigations are few, especially regarding the histopathological conditions of these patients, and the precise mechanisms remain unclear. Nephrocalcinosis can cause end-stage kidney disease if extensive, as observed in the present case.